Excavations at Mendes : a Volume 2 The Dromos and Temple Area - Redford, Donald Bruce (Culture and History of the Ancient Near East, 2020)
The second volume of Excavations at Mendes furthers the publication of our archaeological work at the site of Tel er-Rub'a, ancient Mendes, in the east central Delta. Mendes is proving to be one of the most exciting sites in the Nile Delta. Occupied from prehistoric times until the Roman Period, Mendes reveals the nature of a typical Late Egyptian city, its distribution of economy, and demography. The discoveries reported on in this volume were wholly unexpected, and bear meaning fully on Ancient Egyptian history: these include the prosperity and size of the original Old Kingdom city, the major contributions of Ramesses II and Amasis to the monumental nature of the city, and the role of the city in the period c. 600-100 B.C. as an entrepot for Mediterranean trade.